Red Wine Inspired Chromophores as Photodynamic Therapy Sensitizers. (9th August 2022) - Martins, Lucas M. O. S.; Wang, Xuhui; Silva, Gustavo T. M.; Junqueira, Helena C.; Fornaciari, Bárbara; Lopes, Lohanna F.; Silva, Cassio P.; Zhou, Peng; Cavalcante, Victor F.; Baptista, Mauricio S.; Quina, Frank H.
Abstract: Hydroxypyranoflavylium (HPF) cations are synthetic analogs possessing the same basic chromophore as the pyranoanthocyanins that form during the maturation of red wine. HPF cations absorb strongly in the visible spectral region, and most are fluorescent, triplet‐sensitize singlet oxygen formation in solution and are strong photooxidants, properties that are desirable in a sensitizer for photodynamic therapy (PDT). The results of this study demonstrate that several simple HPF dyes can indeed function as PDT sensitizers. Of the eight HPF cations investigated in this work, four were phototoxic to a human cervical adenocarcinoma cell line (HeLa) at the 1–10 μmol dm −3 level, while only one of the eight compounds showed noticeable cytotoxicity in the dark. Neither a Type I nor a Type II mechanism can adequately rationalize the differences in phototoxicity of the compounds. Colocalization experiments with the most phototoxic compound demonstrated the affinity of the dye for both the mitochondria and lysosomes of HeLa cells. The fact that relatively modest structural differences, e.g., the exchange of an electron‐donating substituent for an electron‐withdrawing substituent, can cause profound differences in the phototoxicity, together with the relatively facile synthesis of substituted HPF cations, makes them interesting candidates for further evaluation as PDT sensitizers. Abstract : Pyranoflavylium dyes exhibit structure‐dependent phototoxicity for HeLa cells.